Fermented Ginger Extract in Natural Deep Eutectic Solvent Enhances Cytotoxicity by Inhibiting NF-κB Mediated CXC Chemokine Receptor 4 Expression in Oxaliplatin-Resistant Human Colorectal Cancer Cells - Ko-Chao Lee; Kuen-Lin Wu; Shun-Fu Chang; Hsin-I Chang; Cheng-Nan Chen; Yih-Yuan Chen (MDPI AG, 2022)
Ginger extracts have been shown to have health-promoting pharmacological activity and beneficial effects, including antioxidant and anticancer properties. The extraction of ginger by natural deep eutectic solvents (NaDES) has been shown to enhance bioactivity, but the cytotoxicity of NaDES extracts needs to be further determined. Signaling through the CXC chemokine receptor 4 (CXCR4) expressed on colorectal cancer (CRC) cells has a pivotal role in tumor cell chemosensitivity. Oxaliplatin is a third-generation platinum compound used as an effective chemotherapeutic drug for CRC treatment. However, whether ginger extract and oxaliplatin could induce a synergistic cytotoxic effect in oxaliplatin-resistant CRC cells through modulating CXCR4 expression is not known. In this study, oxaliplatin-resistant HCT-116 (HCT-116/R) cells were generated first. Ginger was extracted using the NaDES mixture betaine/lactate/water (1:2:2.5). Lactobacillus reuteri fermentation of NaDES-ginger extract increased the total polyphenol content (12.42 mg gallic acid/g in non-fermented NaDES-ginger extract and 23.66 mg gallic acid/g in fermented NaDES-ginger extract). It also increased the antioxidant activity by about 20-30% compared to non-fermented NaDES-ginger extract. In addition, it achieved low cytotoxicity to normal colonic mucosal cells and enhanced the anticancer effect on HCT-116/R cells. On the other hand, the inhibition of NF-κB activation by fermented NaDES-ginger extract significantly decreased the CXCR4 expression (p < 0.05) in HCT-116/R cells. The inactivation of NF-κB by pharmacological inhibitor pyrrolidine dithiocarbamate further enhanced the fermented NaDES-ginger extract-reduced CXCR4 expression levels (p < 0.05). Moreover, fermented NaDES-ginger extract could synergistically increase the cytotoxicity of oxaliplatin by inhibiting CXCR4 expression and inactivating NF-κB, resulting in HCT-116/R cell death. These findings demonstrate that fermented NaDES-ginger extract reduces the NF-kB-mediated activation of CXCR4 and enhances oxaliplatin-induced cytotoxicity in oxaliplatin-resistant CRC cells.